#TITLE_ALTERNATIVE# - S. EFFENDI (NIM : 12207059), ALBERRIDHO
In planning a development for hydrocarbon field, the history of reservoir deliverability is needed. Reservoir Deliverability is used for analyzing the treatment method to be implied for the reservoir. For multi-layer gas wells, the method in determining deliverability of reservoir is a little bit complicated than for single-layer wells, because the transient test for each layer have to be conducted in order to get the deliverability of each layer. In this study, measurement of each layer deliverability is performed using data records from production logging tools, and those tools should record flow condition in tubing for several rate values. Success of this study can be evaluated by validating the results with production data. Result of this calculation is expected to be a reference for analyzing reservoir condition, and for decision-making process to choose the best treatment or stimulation that will be implied.